2020
DOI: 10.1002/oa.2921
|View full text |Cite
|
Sign up to set email alerts
|

Specialized wool production economy of prehistoric farmstead of Chap I in the highlands of Central Tian Shan (Kyrgyzstan)

Abstract: Agro‐pastoral economies of prehistoric populations of Central Tian Shan highlands (2,000 masl and higher) have been poorly studied to date. Currently, we lack a general understanding of mobility and seasonality patterns of livestock herding and also lack knowledge about management strategies for particular productive goals in these high mountain valleys. In this paper, we report the results of the first systematic zooarchaeological analysis from the Final Bronze Age–Early Iron Age settlement Chap I located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The rise in δ 15 N values during the Final Bronze Age and Early Iron Age points towards an intensification of the pastoral economy and increased consumption of animal products. Recent zooarchaeological analysis from Early Iron Age Chap I has shown that caprine animals were exploited for secondary products (wool and milk) as well as meat (Ananyevskaya et al 2020b). Advances in agriculture and the intensification of field manuring may also have contributed to the overall rise in δ 15 N values in humans (Fraser et al .…”
Section: Discussionmentioning
confidence: 99%
“…The rise in δ 15 N values during the Final Bronze Age and Early Iron Age points towards an intensification of the pastoral economy and increased consumption of animal products. Recent zooarchaeological analysis from Early Iron Age Chap I has shown that caprine animals were exploited for secondary products (wool and milk) as well as meat (Ananyevskaya et al 2020b). Advances in agriculture and the intensification of field manuring may also have contributed to the overall rise in δ 15 N values in humans (Fraser et al .…”
Section: Discussionmentioning
confidence: 99%
“…Ten mandibular second (M/2) or third molars (M/3) from domesticated sheep and goats were recovered from the well‐dated occupational strata of Chap‐1 (Motuzaite Matuzeviciute, Tabaldiev, et al, 2020), which met the inclusion criteria of having a crown height greater than 2 cm and having at least one loph with a complete buccal portion (Table S1). Although having comparative isotopic data from domesticated cattle would give a more complete picture of animal management strategies, Bos M/2s or M/3s were not recovered from Chap‐1 (Ananyevskaya et al, 2021). For a modern comparative dataset from wild bovids, we obtained two mandibular M/2s and M/3s each from two modern Siberian ibex ( Capra sibirica ) from snow leopard kill sites in the Jeti‐Oguz nature reserve of Kyrgyzstan (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Because the species of the analyzed teeth were not determined with biomolecular methods such as ZooMS (Zooarchaeology by Mass Spectrometry) (Buckley et al, 2010), and could not be reliably differentiated based on dental morphology, the specific goals of production for sheep or goats at Chap-1 cannot be identified. Zooarchaeological research at Chap-1 identified kill-off patterns of caprines (presumably sheep) favoring survivorship of older animals, suggesting a strategy of wool production (Ananyevskaya et al, 2021).…”
Section: Manipulation Of Animal Birthsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the submission of our original paper in 2018, additional zooarchaeological research in this region has been published, which further expands the data beyond basic presence/absence tables. For example, at the high-altitude site of Chap 1, Kyrgyzstan, zooarchaeological analysis was supported by ZooMS (zooarchaeology by mass spectrometry), suggesting that wool-based pastoralist strategies were likely part of a complex agropastoral lifeway (Ananyevskaya et al 2021;Taylor et al 2018b). Further developing this model, at the nearby site of Aigyrzhal-2, relatively few animal bones were recovered, but evidence for cereal processing was identified (Motuzaite Matuzeviciute et al 2017).…”
Section: Ongoing Research In Central Asian Archaeologymentioning
confidence: 99%